Literature Communication Health Reproductive Education of Youth in Anticipation of Early Marriage - Novianti, Dewi; Fatonah, Siti (RSF Conference Series: Business, Management and Social Sciences, 2021)
The high number of cases of early marriage in Bantul raises its problems. Communication literacy Adolescent reproductive health is still low, so the researchers conducted this study. Research on communication literacy, adolescent reproductive health, education aims to: knowing the knowledge of adolescent reproductive education in Sorowajan, Bantul. Second, the researcher wants to provide literacy in reproductive education health communication for adolescents in Sorowajan, Bantul. This research method is descriptive qualitative, by conducting interviews and Focused Group Discussions with the youth of Bantul's Sorowajan Village According to the study's findings, many teenagers who marry at a young age do so due to a lack of knowledge about adolescent reproductive health, poverty, and a lack of education. The government has carried out adolescent reproductive education through several programs, including the National Family Planning Coordinating Board (BKKBN) which has established Youth Family Development (BKR) groups whose targets are families with teenage children. Academics need to help the government carry out communication literacy on adolescent reproductive health, which in this case the researcher and the team have already done it.